Optimizing the Role of Election Institutions in the Implementation of Fair Regional Elections - Rofiatunnisa, Rasyida (Penerbit Mandalika Indonesia, 2024)
The role of electoral institutions in ensuring fair and just regional elections (Pilkada) is crucial in strengthening democracy. This study aims to optimize the function of electoral institutions in organizing equitable regional elections in Indonesia. Using a qualitative research approach with literature review and library research methods, this study examines various regulations, academic discussions, and best practices related to electoral governance. The research findings indicate that challenges such as political intervention, weak law enforcement, and lack of transparency hinder the effectiveness of electoral institutions in ensuring fairness. Strengthening institutional independence, improving regulatory frameworks, and enhancing monitoring mechanisms are essential to achieving an equitable electoral process. This study also highlights the importance of public participation and collaboration between stakeholders, including civil society organizations and independent election monitors, to enhance electoral integrity. Furthermore, the implementation of technology-based solutions, such as e-voting and real-time monitoring, is recommended to increase efficiency and accountability in election management. The results suggest that an optimized electoral institution plays a pivotal role in promoting a fair democratic process by ensuring impartiality, preventing electoral fraud, and enhancing voter trust. Ultimately, this study contributes to the discourse on democratic governance by proposing strategic recommendations to refine the performance of electoral institutions in organizing just and credible regional elections.